Fetal growth restriction in HIV infected pregnant women - Reis, Helena Lucia Barroso dos (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: a maternal HIV infection may have outstanding consequences to fetal health: mother-to-child transmission and adverse perinatal outcome. After the success in reducing mother–to-child transmission the attention should now be focused on the high proportion of HIV-exposed children either born preterm or with fetal growth restriction. Objective: to determine the preva-lence of preterm birth and fetal growth restriction in HIV-infected women and their relation to the HIV infection stage and non-HIV–associated-comorbidity. Methods: out of 250 deliveries from HIV-infected mothers at a tertiary public university hospital in the city of Vitória, state of Espírito Santo, in the Southeast Brazil, from November 2001 to May 2012, 109 (43.6%) single pregnan-cies with data about the gestational age, HIV status, antiretrovi-ral use, and fetal dimensions were included. Data were extracted from clinical and pathological records, the gestation age was es-timated and the fetal dimensions classified as small, adequate, and large for gestational age according to the pertinent referen-ce standard. Results: preterm birth was observed in 17.4%, low birth weight in 23.9% and small for gestational weight, length, and head and abdominal circumferences in 20.2%, 29.0%, 1.0%, and 43.6%, respectively, without significant variation according to the HIV infection severity or the existence of comorbidity. The concomitant distribution of small for gestational weight, length and abdominal circumference points to an asymmetrical fetal growth restriction. Conclusions: the prevalence of preterm birth and growth restriction were higher than the local prevalen-ce and the expected population distribution in the gestations of HIV-infected, in this casuistry. The findings were unrelated of the stage of the disease (with or without aids) and comorbidities not associated with HIV.